ANALISIS KEMAMPUAN MENGGUNAKAN PUEBI DALAM KARANGAN NARASI SISWA KELAS IV SD NEGERI 35 TALANG UBI - Bella Febbryana Putri; Yasir Arafat; Adrianus Dedy (Universitas Negeri Medan, 2021)
Abstract : The purpose of the study was to describe the ability to use PUEBI in the narrative essays of fourth grade students at SD Negeri 35 Talang Ubi. This research is a qualitative research method based on the philosophy of postpositivism. Data collection techniques in this study were carried out by interviews, and documentation. data analysis can be done in 3 (three) ways, namely data reduction, data presentation, and data verification/drawing conclusions. The results showed that the ability to use PUEBI in narrative essays for fourth grade students at SD Negeri 35 Talang Ubi was divided into 5 (five) categories, namely the ability to use PUEBI in narrative essays in the very good category, the ability to use PUEBI in narrative essays in the good category, and the ability to use PUEBI in narrative essays. the narrative essay category is sufficient, the ability to use PUEBI in the narrative essay is in the poor category, the ability to use PUEBI in the narrative essay is in the failed category. Students who have a very good category are 3 students or 12.50%, students who have good are 3 students or 12.50%, students who have sufficient categories are 18 students or as much as 75%, and there are no students who have the ability using PUEBI in narrative essays in the poor and failed categories.Keywords: Ability Analysis, PUEBI, Narrative WritingAbstrak : Tujuan Penelitian adalah untuk mendeskripsikan kemampuan menggunakan PUEBI dalam karangan narasi siswa kelas IV SD Negeri 35 Talang Ubi. Penelitian ini merupakan penelitian metode kualitatif yang berlandasan pada filsafat postpositivisme. Teknik pengumpulan data dalam penelitian ini dilakukan dengan wawancara, dan dokumentasi. analisis data dapat dilakukan dengan 3 (tiga) cara yaitu reduksi data, penyajian data, dan verifikasi data/penarikan kesimpulan. Hasil penelitian di dapatkan bahwa kemampuan menggunakan PUEBI dalam karangan narasi siswa kelas IV SD Negeri 35 Talang Ubi terbagi menjadi 5 (lima) kategori yaitu kemampuan menggunakan PUEBI dalam karangan narasi kategori baik sekali, kemampuan menggunakan PUEBI dalam karangan narasi kategori baik, kemampuan menggunakan PUEBI dalam karangan narasi kategori cukup, kemampuan menggunakan PUEBI dalam karangan narasi kategori kurang, kemampuan menggunakan PUEBI dalam karangan narasi kategori gagal. Siswa yang memiliki kategori baik sekali berjumlah 3 siswa atau sebanyak 12,50%, siswa yang memiliki baik berjumlah 3 siswa atau sebanayak 12,50%, siswa yang memiliki kategori cukup berjumlah 18 siswa atau sebanyak 75%, dan tidak ada siswa yang memiliki kemampuan menggunakan PUEBI dalam karangan narasi pada kategori kurang dan gagal.Kata Kunci: Analisis Kemampuan, PUEBI, Karangan Narasi